THE CONTRACTOR'S ORGANIZATION FOR TERMINATIONS. - Reetz, W. (The Accounting Review, 1945)
Abstract The article presents information on the contractor's organization for terminations. The past several months have seemed to me very much as the pre-invasion months must have seemed to some of the officers and men charged with the responsibility of preparing for the Allied invasion of France. The constant planning and the uncertainty of the exact date when we would be called upon to test our plans have created a feeling of tension quite unlike anything the author has ever experienced before. In great measure, our success in handling contract terminations will depend upon how well we have laid our plans and what we have learned from the little experience afforded us so far. From the observations that most of us have made, it must appear inevitable that the capitulation of Germany will result in drastic cutbacks and cancellations. It will do little good for us to yell and howl that our contracts should not have been canceled. We entered into these contracts. They specifically provided for termination at the convenience of the government- not at our convenience.